2013
DOI: 10.1590/s1981-67232013005000010
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da substituição de cloreto de sódio por cloreto de potássio em pão francês

Abstract: Há uma tendência mundial de redução de sódio nos alimentos industrializados, em função da sua relação com o aumento da pressão arterial. Na medida em que o pão francês é um dos alimentos que mais contribuem para a ingestão de sódio pela população brasileira, o objetivo desta pesquisa foi avaliar a substituição do cloreto de sódio (NaCl) por cloreto de potássio (KCl) neste produto, como forma de atender a essa tendência. Foram avaliadas quatro formulações: a padrão (FP) com 2% de NaCl e a substituição desta por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
6
0
7
Order By: Relevance
“…Belz et al (2012), found values between 3.56 to 5.10 cm 3 .g -1 when using calcium propionate on the microbial shelf-life of salt reduced bread. Ignácio et al (2013) found specific volumes ranging from 3.22 to 4.06 cm Resolution -RDC n. 90 of 18 Dctober 2000 of the National Health Surveillance Agency establishes a maximum limit of 38% moisture to baked breads exclusively with plain wheat flour and/or special purpose flour (semolina/wheat semolina) (Brasil, 2000). Breads produced in this study had moisture between 29.98 and 31.82%, being lower than recommended by Resolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Belz et al (2012), found values between 3.56 to 5.10 cm 3 .g -1 when using calcium propionate on the microbial shelf-life of salt reduced bread. Ignácio et al (2013) found specific volumes ranging from 3.22 to 4.06 cm Resolution -RDC n. 90 of 18 Dctober 2000 of the National Health Surveillance Agency establishes a maximum limit of 38% moisture to baked breads exclusively with plain wheat flour and/or special purpose flour (semolina/wheat semolina) (Brasil, 2000). Breads produced in this study had moisture between 29.98 and 31.82%, being lower than recommended by Resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Breads assays of 2 e 4 were considered more salty by sensory panel, the tests 5, 6 and 7 were considered intermediate salty flavor and tests 1 and 3 were considered the least salty; adopting these assays as to the sodium chloride content, it is obtained optimum tracks for the salty taste, which corresponds to 1.0 to 1.6% of sodium chloride. Ignácio et al (2013) observed in the acceptance test that 30% of salt, relative to the standard 2%, it was not possible to differentiate breads for flavor attribute. Already the formulation with 50% replacement had worse taste compared to standard but received a note of acceptance equivalent to "like slightly".…”
Section: Sensory Quality Of French Breadmentioning
confidence: 96%
See 1 more Smart Citation
“…Para chegar à meta, em geral, seria preciso retirar do cardápio duas colheres de sopa de sal da alimentação diária. Os dados mostraram que a redução do sal e do Na promoveu uma diminuição de 13% das mortes por doenças coronarianas, 8% do número de infartos e 12% dos acidentes vasculares cerebrais (IGNÁCIO et al, 2013).…”
Section: Determinação Dos Teores De Sódio E Potássio Em Refeições Serunclassified
“…O consumo excessivo de alimentos com elevados teores de sal está relacionado com um maior risco de desenvolvimento de hipertensão arterial (IGNÁCIO et al, 2013). Neste sentido, têm sido desenvolvidas diversas iniciativas, um pouco por todo o mundo, visando reduzir as quantidades de sal presentes nos alimentos (WHO, 2013).…”
Section: Introductionunclassified